Passions and the Interests: Political Arguments for Capitalism before Its Triumph (an excerpt) - Albert Otto Hirschman (Journal of Economic Sociology, 2012)
In his book Albert Hirshman (b. 1915), a famous American economist, reconstructs the intellectual climate of the seventeenth and eighteenth centuries to illuminate the intricate ideological transformation that occurred, wherein the pursuit of material interests — so long condemned as the deadly sin of avarice — was assigned the role of containing the unruly and destructive passions of man. The journal «Economic Sociology» publishes an excerpt from the first part «How the Interests are Called upon to Counteract the Passions» of this volume in which Hirshman discusses how a new paradigm indicating the interests as main drivers of human behavior was developed.